Contribution from East Java as the main gate for the new national capital city project (IKN) - Parningotan, Firman; Herawan, Jonathan (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
This research aims to analyze logistics and trade performance in East Java 2024 as a revitalization of Tanjung Perak Port as a hub port with the National Capital City (IKN) development. IKN development, which will continue until 2045, should be captured as a potential for economic growth and development to be used as a source of new economic growth that is resilient and sustainable. This research uses the Analytical Hierarchy Process to see the performance of Tanjung Perak Port with other large ports on the island of Java. It carries out IRIO computation analysis to see the interlinkage of sectors that have the potential to be worked on by East Java Province for IKN development. Research that uses 3 criteria, namely port performance, port productivity, and the multiplier effect with 12 variables, obtains varied results but considers that Tanjung Perak Port is the best port as a port hub with South Kalimantan Province, East Java Province, and can also encourage the Agriculture, Forestry and Fishery; Processing industry; and Wholesale and Retail Trade; Car and Motorbike Repair to provide maximum impact on the regional economy